Understanding the effect of angina on general and dimensions of psychological distress: findings from understanding society - Kang, Weixi (Frontiers in Psychiatry, 2023)
Background The aim of the current study was to investigate how the general and dimensions of psychological distress are affected by angina. Methods First, a confirmatory factor analysis (CFA) was applied to investigate the factor structure of the GHQ-12. Second, a train-and-test approach to predict the expected scores for 1, 081 people with angina based on a model trained on demographics from 8, 821 age and sex-matched healthy controls. Finally, one-sample t-tests were used to determine the differences between the actual psychological distress scores and expected psychological distress scores in participants with angina. Results There were three underlying structures of the GHQ-12 labeled as GHQ-12A (social dysfunction & anhedonia; 6 items), GHQ-12B (depression & anxiety; 4 items), and GHQ-12C (loss of confidence; 2 items). Moreover, participants with angina had more psychological distress as indicated by the GHQ-12 summary score (Cohen’s d=0.31), GHQ-12A (Cohen’s d=0.34), GHQ-12B (Cohen’s d=0.21), and GHQ-12C (Cohen’s d=0.20) comparing to controls. Conclusion The current study implies that GHQ-12 is a valid measure of psychological distress in people with angina, and there is a need to consider the dimensions of psychological distress in angina rather than solely focusing on certain dimensions of psychological distress such as depression or anxiety issues in people with angina. Clinicians should come up with screening tools and interventions to reduce psychological distress in people with angina which can then lead to better outcomes.